2018
DOI: 10.1373/jalm.2017.025346
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Estimation of Drug Intake Day by Microsegmental Analysis of a Strand of Hair by Use of Internal Temporal Markers

Abstract: Background: Segmental hair analysis can be useful for estimating the time of drug intake. However, this estimation is currently only accurate to within several months. We previously conducted microsegmental analysis of a strand of hair to visualize drug distribution at a spatial resolution of 0.4 mm, which corresponds to daily hair-growth length.Herein, we describe a procedure for accurately estimating the day of drug intake by using internal temporal markers (ITMs) to mark a timescale in the analyzed strand o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 16 publications
(21 reference statements)
0
25
0
Order By: Relevance
“…Ideally, the average individual hair growth rate should be applied but is usually not known. Kuwayama et al 25 used a so‐called “internal temporal marker” by ingestion of a known substance at defined time points after a suspected drug intake thus enabling to calculate the time point of administration based on the individual (single) hair growth rate, deduced from the position of the marker within the hair shaft. In our study, a different approach has been used without the need to ingest a further substance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, the average individual hair growth rate should be applied but is usually not known. Kuwayama et al 25 used a so‐called “internal temporal marker” by ingestion of a known substance at defined time points after a suspected drug intake thus enabling to calculate the time point of administration based on the individual (single) hair growth rate, deduced from the position of the marker within the hair shaft. In our study, a different approach has been used without the need to ingest a further substance.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the average individual hair growth rate should be applied but is usually not known. Kuwayama et al25 used a so-called "internal temporal marker" by ingestion of a known…”
mentioning
confidence: 99%
“…The accuracy was almost the same as that in single-dose ingestion, as we previously reported. 12 The absolute average error and its variation for estimating the number of days (Y at Scene 1) were smaller (1.5 ± 1.4 days) than those for X, because Y is independent of the distance between the peaks of ITM and a targeted drug.…”
Section: Discussionmentioning
confidence: 87%
“…In our previous reports [10][11][12][13] and preliminary study, we obtained typical drug distribution curves, as shown in Figure 1. When a singledose drug is ingested, the distribution curve has a major peak derived from drug incorporation via the bloodstream (Figure 1B).…”
mentioning
confidence: 97%
“…MALDI mass spectrometric imaging requires less sample preparation but is less sensitive than LC/MS/MS. Kuwayama et al (1,11), in what they call microsegmental analysis, used 0.4-mm segments of hair. This length of hair approximately corresponds to the average daily growth of human scalp hair.…”
Section: Uttam Garg*mentioning
confidence: 99%